Pengaruh Faktor Risiko terhadap Kejadian Peningkatan Kadar Enzim Transaminase pada Pasien Covid-19 dengan Terapi Tocilizumab - Nasution, Izza Aulia Rizqika; Andrajati, Retnosari; Syafhan, Nadia Farhanah; Imaniar, Rania (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: Tocilizumab is an anti-IL-6 which is recommended as cytokine release syndrome therapy in the treatment of Covid-19. One of the side effects of tocilizumab that can occur is hepatotoxicity, from mild elevated transaminases to severe drug-induced liver injury (DILI). Currently, research related to tocilizumab hepatotoxicity and the risk factors affecting Covid-19 patients is limited and still needs to conduct. This research is an observational study with cross-sectional design. Data collection was carried out retrospectively using secondary data obtained from medical records department, patients with Covid-19 at Universitas Indonesia Hospital in 2020-2021. Patients confirmed with positive Covid-19 receiving Tocilizumab therapy in medical record were included in this study. Patient demographics, clinical diagnoses, laboratory examinations, history of others medication were also reviewed. Patients with less than 18 years old, incomplete medical record data, and referred to other hospitals were excluded. The sampling technique used was total sampling, namely all patients who met the inclusion criteria were taken as subject in this research. Chi-square test was used to analyze the relationship between each risk factors and the incidence of elevated transaminases. The results of Chi-square test showed that several risk factors significantly increased the incidence of elevated transaminases in patients given tocilizumab therapy, including age, obesity, diabetes mellitus, and ceftriaxone as antibiotic therapy.